2009
DOI: 10.1182/blood-2008-07-168609
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells prime alloreactive T cells to mediate graft-versus-host disease as antigen-presenting cells

Abstract: Dendritic cells (DCs) can be classified into 2 distinct subsets: conventional DCs (cDCs) and plasmacytoid DCs (pDCs). cDCs can prime antigen-specific T-cell immunity, whereas in vivo function of pDCs as antigen-presenting cells remains controversial. We evaluated the contribution of pDCs to allogeneic T-cell responses in vivo in mouse models of graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation by an add-back study of MHCexpressing pDCs into major histocompatibility compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 55 publications
3
79
1
Order By: Relevance
“…Recipient cDCs 23 and pDCs 24 in isolation are able to induce allogeneic T-cell responses after transfer into MHC class II Ϫ/Ϫ recipients in vivo after conditioning. Although elegant, these studies demonstrate only that cDCs and pDCs in isolation can initiate GVHD, but their relative contribution to this process when all APC fractions are intact remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recipient cDCs 23 and pDCs 24 in isolation are able to induce allogeneic T-cell responses after transfer into MHC class II Ϫ/Ϫ recipients in vivo after conditioning. Although elegant, these studies demonstrate only that cDCs and pDCs in isolation can initiate GVHD, but their relative contribution to this process when all APC fractions are intact remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the state of maturation of pDCs seems to be crucial in their ability to trigger GVHD. On the one hand, total-body irradiation induces inflammation and maturation of pDCs, which can subsequently activate T cells (6). On the other hand, Banovic et al (34) showed that precursors of pDCs, but not mature pDCs, can attenuate the symptoms of GVHD, emphasizing the differential functions of pDCs depending on the environment and the model of GVHD.…”
Section: The Decrease In Splenic Cd4mentioning
confidence: 99%
“…In contrast, the role of APCs in chronic GVHD was recently emphasized by the observation that costimulation of donor T cells through CD80 or CD86 on either host or donor APCs is necessary to induce chronic GVHD (32). pDCs are especially involved in the physiopathology of GVHD because the adoptive transfer of mature pDCs exacerbates GVHD, and they can stimulate donor T cells to trigger GVHD in the absence of other APCs (6,33). Yet, the state of maturation of pDCs seems to be crucial in their ability to trigger GVHD.…”
Section: The Decrease In Splenic Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, host pDCs have been shown to induce GVHD in a TLR-independent manner. 32 In addition, GVHD prevents the maturation of donor pDCs. 33 Thus, the role of pDCs in acute GVHD is still controversial and confirmatory studies about their functions are necessary before a therapeutic approach based on this mechanism can be contemplated.…”
Section: Sensors Of Gvhdmentioning
confidence: 99%